From the Editor on Women’s Health: pregnancy, complications, future - Pacheco-Romero, José (2019)
In the last few months, we have found interesting new studies on women’s health related to pregnancy and its long and short-term complications. Our specialty needs to know these advances as input for our medical practice and to prevent consequences in the long term.